STRATEGI KOMUNIKASI ORGANISASI SATUAN PENGAMANAN DI PT. PANDAN BAHARI SHIPYARD TANJUNG UNCANG KOTA BATAM - Alimudin, Alimudin; Syafi'i, Muhammad (LPPM Universitas Putera Batam, 2020)
This research is done with the aim to know the organizational communication strategy used by PT Pandan Bahari Shipyard Security unit in improving security in the company. The research was conducted at PT Pandan Bahari Shipyard Tanjung Uncang Kota Batam. This research uses descriptive qualitative research method. Collection of data obtained based on the results of the way, observation and documentation. Then a support strategy, this strategy focuses more on the development of valuable partners through cooperation between institutions such as police binmas and navy. Then the strategy of support, this strategy focuses more on the development of valuable partners through cooperation between institutions such as the police binmas and navy. And the last integration strategy, in this case the head of security safeguards always coordinate both through breifing and meeting with members. Keywords : communication strategy, for Security unit organizations.